Climate change- lower electricity prices and increasing demand. An application to the Nordic Countries - Karina Gabrielsen; Torstein Bye; Finn Roar Aune (Statistics Norway, Research Department, 2005)
Concentration of greenhouse gases in the atmosphere influences the climate, which then alters the amount of primary energy for countries or regions where hydropower and wind power constitute important parts of the energy supply. Besides, the demand effect of temperature increases may be large in economies where heating and air-conditioning demand a large share of total energy. In this article, we apply climate change calculations from natural science and detailed inflow data from the authorities to estimate the change in primary energy supply of the hydropower-dominated Nordic electricity market. The estimated inflow model shows an increase in primary inflow in the next 40 years of 6-15% in the Nordic countries. An estimated temperature model shows a 2-4% initial drop in demand in the same time period, because of increasing temperature. Within the context of a perfect-competition electricity market model, we simulate the total market outcome. As primary supply increases, the production cost decreases, prices drop and the total demand increases as the price effect dominates the temperature effect. Since the hydropower plants are located away from large consumer groups, the stress on the transmission networks is dramatic for some regions, which in the next phase may trigger new investments in transmission network capacities.
Keywords: Q11; Q21; Q42; 330; Climate change; electricity market